An Anatomic Basis for Revision Rhinoplasty - Pearlman, Steven J.; Talei, Benjamin A. (Facial Plastic Surgery, 2012)
As the popularity of rhinoplasty has increased, so have the expectations of both patients and surgeons alike. Revision rhinoplasty has become an evolving field with unique challenges. One must first address the patient's specific concerns and emotional issues. To properly repair the inadequacies of a failed rhinoplasty, the surgeon must thoroughly analyze and understand the anatomic causes leading to why the patient needs revision surgery.
Keywords: revision rhinoplasty; nasal valve; saddle deformity; rhinoplasty complication; nasal tip deformity